PHP and MySQL for Dynamic Web Sites: Visual QuickPro Guide (2nd Edition) - Ullman, Larry (Peachpit Press, 2011)
It hasn't taken Web developers long to discover that when it comes to creating dynamic, database-driven Web sites, MySQL and PHP provide a winning open source combination. Add this book to the mix, and there's no limit to the powerful, interactive Web sites that users can create. With step-by-step instructions, complete scripts, and expert tips to guide readers, veteran author and database designer Larry Ullman gets right down to business: After grounding readers with separate discussions of first the scripting language (PHP) and then the database program (MySQL), he goes on to cover security, sessions and cookies, and using additional Web tools, with several sections devoted to creating sample applications. This guide is indispensable for Web designers who want to replace their static sites with something more dynamic. The companion Web site includes source code, support forums, and extra tutorials. In addition to being updated for the most recent releases of MySQL and PHP, this new edition offers 25% new material, including updated examples for improved clarity and comprehension and new installation instructions for PHP, MySQL, and other related technologies.